Reading Aloud and Staging: A Path Towards Literary Narrative Comprehension - Leyva-Ortiz, Jesús Alberto (2020)
This paper shows the results obtained when applying a literary-didactical proposal, which was a successful tool to encourage reading comprehension and gave rich experiences in the teaching of literature. This project was conducted by 32 pre-service teachers and eight professors from the “Benemérita y Centenaria Escuela Normal del Estado de San Luis Potosí” along ten months. To study Mario Benedetti’s novel “La Tregua” (The Truce), the researchers implemented a strategy based on mixing individual reading with reading aloud and role-playing of the book. The results from a sample of 81 participants (40 from the staff and the rest from assistants to the events) show qualitative and quantitative data about the need and importance of this work. At the same time, it illustrates how deep and comprehensive the reading was for readers according to the level of reading efficiency reached. Founding on our word and results, we send it to you for your consideration.